2013
DOI: 10.1016/s1836-9553(13)70163-2
|View full text |Cite
|
Sign up to set email alerts
|

Massage reduced severity of pain during labour: a randomised trial

Abstract: Massage reduced the severity of pain in labour, despite not changing its characteristics and location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 21 publications
2
40
0
4
Order By: Relevance
“…Others massaged the sacral region to relieve them of painful contractions of labour and they taught them as well to do it themselves. Similar findings revealed that massage decreases labour pain intensity [ 26 ] and helps to lessen dependence on pain reliefs [ 27 ]. Some midwives explained and shared with the nullipara the nature and rationale of labour pain in order to prepare their minds for the pain.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Others massaged the sacral region to relieve them of painful contractions of labour and they taught them as well to do it themselves. Similar findings revealed that massage decreases labour pain intensity [ 26 ] and helps to lessen dependence on pain reliefs [ 27 ]. Some midwives explained and shared with the nullipara the nature and rationale of labour pain in order to prepare their minds for the pain.…”
Section: Discussionmentioning
confidence: 56%
“…The widely used non-pharmacological approaches are deep breathing exercises and positioning [ 12 ] perhaps because there is comfort and diversion of attention from the pain. Other methods such as massage decrease labour pain [ 26 ], lessen dependence on analgesics [ 27 ] and decrease anxiety especially when performed with a comforting touch [ 28 ]. Midwives can also give support through praises [ 29 ], therapeutic touch [ 30 ], as well as explaining or informing women of labour progress [ 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The database searches retrieved 348 nonduplicate records, of which 320 were excluded after title/abstract screening. The remaining 28 full texts were assessed for eligibility, of which 17 articles were excluded because they were commentaries, [ 20 – 24 ] conference presentations, [ 25 ] did not investigate LBP or PGP during pregnancy, [ 26 – 28 ] did not include manual therapies, [ 29 , 30 ] women were not investigated or treated antenatal, [ 31 33 ] or the trials were not randomized. [ 34 – 36 ] The remaining 11 full-text articles, reporting on 10 studies, were included.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 18 ] The authors of a systematic review have reported that the hot bath therapy reduced pain in women with a cervical dilation of 8 to 9 cm and therefore reduced the need for pharmacological analgesia. [ 14 , 19 ] The authors emphasized that nonpharmacological methods are beneficial and presented few side effects and contraindications. Furthermore, nonpharmacological interventions are noninvasive and favor the active participation of the mother during labor.…”
Section: Introductionmentioning
confidence: 99%